PENGARUH MEDIA SOSIAL TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS VIII DI SMP YAYASAN GEMA BUKIT BARISAN KECAMATAN TANJUNG MORAWA - Ruri Maydani; M. Faisal Husna; Dalyanto Dalyanto; Abdul Marif (STKIP Subang, 2025)
Since the outbreak of Covid 19, the education system has changed rapidly. One of the impacts is the learning system using gadgets and social media. This social media has both good and bad impacts. The use of social media, especially among junior high school students of the Gema Bukit Barisan Foundation, also has a positive and negative impact. Where the good impact of using social media is that learning activities become easier, more efficient and save time and a wide range of learning topics. But the bad impact of social media for students is that many students become addicted to social media. Where students become dependent on social media and feel worried if they do not use social media. If left unchecked, it can affect the formation of character in students. With this research, it is hoped that the cooperation of teachers and parents to be able to supervise and limit the use of social media so that bad things that are not wanted in the future can be avoided. In order to realize our hope to make Indonesian children the next generation of the nation with morals and good ethics.